Membangun Sikap “Saling Menyayangi” pada Sesama Siswa Berbasis Sunnah Nabi: Strategi Preventif Bullying di Sekolah - Zainnurrofiq, Muhammad; Rochmawati, Ida; Anggraeni, Nofalia Cindi; Zaki, Muhammad Satrio Wibowo; Zahro, Fatima Azh; Pramudita, Lauhannia; Faizah, Maila; Farangga, Novian Syah; Seninoto, Muhammad Muhajir (Universitas Negeri Makassar, 2025)
Cases of bullying in schools require serious attention due to their physically and psychologically detrimental effects. This community service program aimed to prevent bullying at MI Hidayatul Ulum, Tempel, Krian, Sidoarjo Regency through mentorship and education based on the values of hadith, with the theme “Loving Others is the Prophet’s Sunnah.” The program employed the Community-Based Research (CBR) method, addressing issues identified within the community. Observations and interviews revealed that 51% of students experienced bullying, both physical and verbal. The target participants were students from classes 4A, 4B, 5A, 5B, 6A, and 6B. The educational materials focused on the values of compassion found in the teachings of Prophet Muhammad saw and were combined with additional topics such as the types of bullying, its social impacts, and strategies for preventing and addressing bullying. This program produced significant outcomes. First, there was an increase in students’ understanding of bullying through the lens of the Prophet’s teachings. Second, students demonstrated behavioral changes, shifting from hostile interactions to more compassionate relationships. Third, an anti-bullying commitment was symbolized through bulletin boards, serving as reminders of the importance of maintaining a harmonious and bullying-free school environment.